2008
DOI: 10.1021/np800504w
|View full text |Cite
|
Sign up to set email alerts
|

Endiandric Acid Analogues from the Roots of Beilschmiedia erythrophloia

Abstract: Investigation of the roots of Beilschmiedia erythrophloia has led to the isolation of seven new endiandric acid analogues, erythrophloins A-F (1-6) and beilcyclone A (7), together with 11 known compounds. The structures of 1-7 were determined using spectroscopic techniques. Two constituents, erythrophloin C (3) and suberosol B (8), exhibited antitubercular activity against Mycobacterium tuberculosis H37Rv, showing MIC values of 50 and 28.9 microg/mL, respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
57
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(58 citation statements)
references
References 21 publications
(52 reference statements)
1
57
0
Order By: Relevance
“…Both compounds also exhibited corresponding epoxy-analogues, 4α,5α-epoxybeilschmin A-B and this revealed that epoxidation of the C-4,5 bond would result in reduced anti-tubercular activity. In another study of anti-tubercular activity, Yang et al [18] verified that erythrophloin C showed significant activity against Mycobacterium tuberculosis H37Rv (MIC of 50 µg/mL), comparable to ethambutol (MIC of 6.25 μg/mL).…”
Section: Anti-tubercular Activitymentioning
confidence: 98%
See 1 more Smart Citation
“…Both compounds also exhibited corresponding epoxy-analogues, 4α,5α-epoxybeilschmin A-B and this revealed that epoxidation of the C-4,5 bond would result in reduced anti-tubercular activity. In another study of anti-tubercular activity, Yang et al [18] verified that erythrophloin C showed significant activity against Mycobacterium tuberculosis H37Rv (MIC of 50 µg/mL), comparable to ethambutol (MIC of 6.25 μg/mL).…”
Section: Anti-tubercular Activitymentioning
confidence: 98%
“…Because of their versatile therapeutic traditional uses, extensive phytochemical investigations have been carried out on Beilschmiedia plants which led to isolation of numerous classes of secondary metabolites such as terpenoids, endiandric acid derivatives, essential oils, fatty acids, lignans/neolignans, flavonoids, amide/alkaloids and other components. Endiandric acid derivatives are considered to be the main constituents in Beilschmiedia species and are responsible for many of their biological and pharmacological activities [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the structure of compound 2 was established as 4'-(hydroxy(12-(3-hydroxy-4,6,7-trimethoxyphenanthren-1-yl)ethyl)amino)cyclopenta-1',3'-dienecarbaldehyde, and given a trivial name of beilschglabrine B. The known compounds, lupeol (Yang et al, 2009), taraxerol (Chen et al 1998) and 24-methylenelanosta-7,9-diene-3β-15α-diol (Lue et al, 1998), were identified by comparison of their spectroscopic data with published data.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13] These complex fatty acids, typically isolated as racemic mixtures, were proposed by Black to be the result of a series of consecutive nonenzymatic cyclizations (8πe, 6πe, and DielsAlder) of a polyunsaturated fatty acid precurser. 14 Support for such a mode of biosynthesis was provided by a biomimetic synthesis carried out by Nicolaou.…”
mentioning
confidence: 99%
“…Recent publications have reported antibacterial and anti-inflammatory activity. 9,10,13 Additionally, one analogue was the subject of a patent that claimed it was useful in the treatment of asthma. 7 Given the unique chemical space occupied by these compounds, and the lack of biological activity reported, we checked our plant library to see if any material was available that could yield similar compounds.…”
mentioning
confidence: 99%